Studies in English official historical documents. - Hall, Hubert (Selected essays in history, economics, & social science,, 1908)
This 1908 book was a ground-breaking guide for historians in the use and interpretation of official documentary sources. Hubert Hall examines the topic under three headings - archives, diplomatics, and palaeography. In the first part he treats the history, classification and analysis of English archives. He argues that the user should take into account what once existed as well as what survives. The second part deals with diplomatics, from Anglo-Saxons to the sixteenth century. He calls for greater critical analysis of the different types of official dicuments, something lacking in English when compared to European scholarship. The final part introduces the student to palaeography, and the different kinds of handwriting and contractions met with in official documents. While the book makes no claim to be the definitive work on the subject, it raised the profile of a neglected tool of scholarship, and offers a starting point for further research.